Creation and Activity of Priamursk Military Topographic Department in Late 19th — Early 20th Centuries - E. V. Igumnov (Научный диалог)
The history of the emergence and development of the military topographic service in the Far East in the pre-Soviet period is considered. Close attention is paid to the prerequisites for the creation of the Amur military topographic department. The role of the ranks of the Corps of Military Topographers and the East Siberian Military Topographic Department in the annexation and development of the Amur Region and the Ussuri Region in the second half of the 19th century is shown. Changes in the numerical strength of the Amur military-topographic department are traced. The significance of topographic and astronomical-geodetic works for solving the problems of the foreign policy of the Russian Empire in the East Asian region is revealed. The activities of the Amur department in Manchuria, the participation of military topographers in the events of the Russian-Japanese war of 1904—1905 are disclosed in detail. The contribution of the Amur department to the economic development of the south of the Far East and Transbaikalia is revealed. The work of topographers in the framework of auxiliary measures for the construction of the Transsib and the Amur railway, during geological research in the Primorsko-Amur gold-bearing regions is presented. In conclusion the results are summarized, data that confirm that the activities of military topographers in the Far East were not limited to the performance of some military functions and was intended to ensure the interests of various government institutions and departments is provided.